STUDI FENOMENOLOGI: PENGALAMAN KELUARGA SEBAGAI CAREGIVER DALAM MERAWAT PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUD DR. DRADJAT PRAWIRANEGARA TAHUN 2024 - Rahmawati, Dewi; Lusiani, Milawati; Nurmalasari, Elda (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2024)
The prevalence of chronic kidney failure cases undergoing hemodialysis is increasing due to hypertension and diabetes. This makes the problem itself not only for patients but also for families as caregivers who provide care. The role of the family in family care starts from remediation so prevention, treatment and rehabilitation are very important. The purpose of this study is to find out the experience of families as caregivers in caring for chronic kidney failure patients undergoing hemodialysis at Dr. Dradjat Prawiranegara Hospital in 2024. This research method uses a qualitative design with a phenomenological study with a purposive sampling technique, analyzed by the Collaizi method using Open Code version 3.6 through the transcribing process, identifying significant statements, formulating the meaning of each significant statement, grouping meanings into categories, categorizing each unit of meaning into one meaning theme, describing the themes formed,  carried out the process of validating the results of the provisional analysis to participants through the HP IPhone Xr communication tool via WhatsApp.  The results of the research obtained a theme that became a new insight: the first response when making hemodialysis decisions, the feeling of care, the support system of the family in facing hemodialysis patients, feeling that they have a heavy responsibility, a glimmer of hope for the future of family members. There is a need for a family meeting with the participation of health workers in approaching caregivers in making care planning and activating the role of the community of chronic kidney failure survivor associations to be able to provide mental and spiritual strength.